2009
DOI: 10.1002/app.30187
|View full text |Cite
|
Sign up to set email alerts
|

Modification of cellulose acetate with oligomeric polycaprolactone by reactive processing: Efficiency, compatibility, and properties

Abstract: Oligomeric polycaprolactone (oPCL) was used for the modification of cellulose acetate by reactive processing in an internal mixer at 180 C, 50 rpm, 60 min reaction time, and 45 wt % caprolactone (CL) content. The product of the reaction was characterized by several analytical techniques and its mechanical properties were determined by dynamic mechanical thermal analysis and tensile testing. The synthesized oPCL contained small and large molecular weight components. The small molecular weight fraction plasticiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…For biomacromolecule (e.g., cellulose, starch) films with or without external plasticizers, mechanical strength mainly depends on the hydrogen bonds. External plasticization (a replacement of hydrogen bridges acting among the chains by the interaction of the plasticizer and the groups forming those bridges) leads to a considerable decrease of strength because of the decreasing hydrogen bonds. ,, In other words, external plasticization can improve the film-forming performance of biopolymers at the cost of decreasing their tensile strength. In this work, continuous xylan film without external plasticizer cannot be formed because strong hydrogen bonds caused strong internal stress, resulting in cracks and defects within the film .…”
Section: Resultsmentioning
confidence: 99%
“…For biomacromolecule (e.g., cellulose, starch) films with or without external plasticizers, mechanical strength mainly depends on the hydrogen bonds. External plasticization (a replacement of hydrogen bridges acting among the chains by the interaction of the plasticizer and the groups forming those bridges) leads to a considerable decrease of strength because of the decreasing hydrogen bonds. ,, In other words, external plasticization can improve the film-forming performance of biopolymers at the cost of decreasing their tensile strength. In this work, continuous xylan film without external plasticizer cannot be formed because strong hydrogen bonds caused strong internal stress, resulting in cracks and defects within the film .…”
Section: Resultsmentioning
confidence: 99%
“…They also explain this with an increase in viscosity due to branching reaction and network structure formation. Furthermore, Klébert [ 19 ] as well as Klébert et al [ 20 ] reported a similar strong increase in torque during melt grafting of CA with different caprolactones.…”
Section: Resultsmentioning
confidence: 65%
“…Often, external plasticizers were added to improve processing and homogenization and to facilitate the grafting reaction in the molten state due to better access to the functional groups. Nevertheless, in most cases long reaction times and large quantities of catalysts and monomers are necessary for sufficiently high grafting yields [17,18,19,20,21,22]. Thus, most of the processing conditions used in these studies are not viable for typical compounding processes prohibiting economic feasibility of the processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the biomacromolecule films (e.g., cellulose, starch) with or without external additives, mechanical strength mainly depends on the hydrogen bonds. External additives leads to a considerable decrease of strength due to the decreasing hydrogen bonds 49 50 . In other words, the additives can improve the film-forming performance of biopolymer at the cost of decreasing their tensile strength.…”
Section: Resultsmentioning
confidence: 99%